2015
DOI: 10.1186/s13104-015-1672-0
|View full text |Cite
|
Sign up to set email alerts
|

Guillain–Barre syndrome following dengue fever and literature review

Abstract: BackgroundDengue is an arboviral infection that classically presents with fever, joint pain, headaches, skin flush and morbilliform rashes. The incidence of neurological symptoms and complications in dengue varies from 1 to 25 % that include encephalopathy, Guillain–Barre syndrome (GBS), acute motor weakness, seizures, neuritis, hypokalaemic paralysis, pyramidal tract signs, and a few more. Dengue fever as an antecedent infection in GBS is uncommon.Case presentationA 34-years-old Sri Lankan Sinhalese male pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
1
4

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(33 citation statements)
references
References 13 publications
(21 reference statements)
1
27
1
4
Order By: Relevance
“…In the majority of cases, the electrodiagnosis was in keeping with AIDP with several authors describing prolonged distal latencies, slow conduction velocities and delayed F waves 30–34 36 37. In three cases where electrophysiology data were not provided, the authors concluded axonal subtypes of GBS (1 AMAN and 2 acute motor and sensory polyneuropathy) 35 38.…”
Section: Methodsmentioning
confidence: 78%
“…In the majority of cases, the electrodiagnosis was in keeping with AIDP with several authors describing prolonged distal latencies, slow conduction velocities and delayed F waves 30–34 36 37. In three cases where electrophysiology data were not provided, the authors concluded axonal subtypes of GBS (1 AMAN and 2 acute motor and sensory polyneuropathy) 35 38.…”
Section: Methodsmentioning
confidence: 78%
“…Zika fetal disorder accounts for the aforementioned complexities along with the neonatal neurological impairment during pregnancy. GBS has been observed to sporadically follow dengue viral infection910 but is apparently more severe in the case of ZIKV due to the incidence of teratogenic lesions11. ZIKV has been identified by PCR in fetuses, and Zika virus particles have been detected by electron microscopy in the fetal central nervous system in high concentrations5.…”
mentioning
confidence: 99%
“…Recent infectious diseases caused by agents such as Zika virus, Dengue virus, Chikungunya virus or influenza virus as primary triggers of GBS can be ruled out if the onset of the neurological signs and symptoms occurs during the dry season, or when no infectious disease outbreak is recorded where the patient lives or the place the patient has visited on travel. Viral infections typically present a seasonality pattern with a peak during the wet season (Cao‐Lormeau et al, ; Cortese et al, ; Oehler et al, ; Pastula et al, ; Ralapanawa, Kularatne, & Jayalath, ; Simon et al, ). Other exclusion criteria include a clinical presentation that may not fit completely to infection, e.g., no myalgia, no joint pain, no retrobulbar pain, no sign or symptoms suggestive of Campylobacter enteritis or Mycoplasma infection as possible triggers of GBS (Ang et al, ; Sharma et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…However, it is interesting that an association between HPV vaccination and GBS is frequently made, in spite of GBS following HPV vaccination being a very rare event (Katoulis et al, 2010;Ojha et al, 2014). Cortese et al, 2012;Oehler et al, 2015;Pastula et al, 2017;Ralapanawa, Kularatne, & Jayalath, 2015;Simon et al, 2016). Other exclusion criteria include a clinical presentation that may not fit completely to infection, e.g., no myalgia, no joint pain, no retrobulbar pain, no sign or symptoms suggestive of Campylobacter enteritis or…”
Section: Arsenic Neuropathymentioning
confidence: 99%